Platelet antiaggregant activity of Hypericum perforatum extracts - Maria Céu Monteiro; Daniela Costa; Alberto Dias; Luís Bernardo Pina-Cabral; António Almeida-Dias; Jorge Machado; Maria Begoña Criado (Elsevier, 2024)
Background: In addition to its potential use as an antidepressant, different studies have shown that Hypericum perforatum (HP) can have antibacterial, antioxidant, and antiviral properties. Despite this potential, most of the therapeutic bioactivities attributed to HP need further scientific support. In a previous study we found an inhibitory effect of HP in platelet activation markers. So, in the present work we investigate the effect of HP in another aspect of platelet function, platelet aggregation. Methods: First, the effect of different concentrations of the total alcoholic extract of HP on platelet aggregation was studied in 9 healthy donors by aggregometry methods using collagen as agonist. After that, to obtain dose-effect curves, 3 experiments were carried out independently in a single individual using collagen, adenosine diphosphate and epinephrine as agonists. Results: Our results reveal a marked inter-individual variability and a significant dose-dependent decrease of aggregation responses induced by collagen in the presence of HP extracts (mean of minimum inhibition: 8 % at a dose of 0.068 mg es/ml and mean of maximum inhibition: 43 % at a dose of 0.456 mg es/ml). With the results obtained it was possible to obtained a IC50 value of 0.34 mg es/ml. Conclusions: We can conclude that HP has a dose-dependent inhibitory effect on platelet function (activation and aggregation responses), therefore, our results suggest that HP may be recognized as an herbal medicine with anti-platelet properties.